ISIS propaganda: a full-spectrum extremist message - Baele, Stéphane J.; Boyd, Katharine A.; Coan, Travis G. (Causes and consequences of terrorism, 2020)
This text offers a comprehensive overview and analysis of the Islamic State's use of propaganda. Combining a range of different theoretical perspectives from across the social sciences, and using rigorous methods, the authors trace the origins of the Islamic State's message, laying bare the strategic logic guiding its evolution, examining each of its multi-media components, and showing how these elements work together to radicalize audiences' worldviews.